Exploring the therapeutic potential of Ashwagandha (Withania somnifera) supplementation in alleviating stress and stress-related disorders - Kuśmierska, Martyna; Kuśmierski, Jakub; Kwaśniewska, Oliwia (Quality in Sport, 2024)
Withania somnifera, also known as Ashwagandha, is a key herb in Ayurvedic medicine, celebrated for its ability to rejuvenate and promote longevity. It is believed to support overall wellness, offering neuroprotective, anti-inflammatory, and adaptogenic benefits. This study aims to evaluate how Ashwagandha (Withania somnifera) supplementation impacts stress levels, psychological well-being, and resilience, assessing its overall effectiveness as an adaptogen. Stress, be it physical or psychological, activates a response involving the nervous, endocrine, and immune systems through various mechanisms, initially aiding in handling challenges but becoming detrimental when perceived as intense, repetitive, or prolonged, contributing to conditions like depression, anxiety and cognitive decline. Ashwagandha reduces morning cortisol and DHEA-S levels and increases heart rate variability. It improves sleep quality, alleviates anxiety symptoms, and may help with depression due to its components, such as alkaloids and withanolides. Additionally, it reduces fatigue and enhances overall well-being and happiness. It is important that Ashwagandha supplementation is safe and does not cause side effects, making it an attractive alternative for supporting health and well-being. Ashwagandha supplementation, due to adaptogenic qualities, appears promising in addressing stress and stress-related disorders, as well as enhancing overall well-being. Further research is warranted to fully explore its potential role in conventional health strategies.